2015
DOI: 10.1186/s40064-015-1025-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro somatic embryogenesis and plantlet regeneration from immature male inflorescence of adult dura and tenera palms of Elaeis guineensis (Jacq.)

Abstract: We report here a method for plant regeneration through somatic embryogenesis from explants collected from immature male inflorescence of adult oil palm cultivated in India. Callus induction was successful from tissues of immature male inflorescence collected from both dura and tenera varieties of oil palm. A modified Y3 (Eeuwens) media supplemented with several additives and activated charcoal (3%) were used for the experiments. Out of four different auxin treatments, 4-amino-3,5,6-trichloro-2-pyridinecarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 15 publications
3
27
0
8
Order By: Relevance
“…This result may indicate that low concentrations of NAA were suitable for SE in K. paniculate. In the studies of other woody plants, the frequency of somatic embryogenesis varied from 4.9% to 63% [27][28][29]34], and the frequency of SE in K. paniculate was at a high level in the research. Similarly, NAA has been reported to influence somatic embryo development in holm oak and Eucalyptus camaldulensis Dehn.…”
Section: Effect Of Plant Growth Regulators On Somatic Embryogenesismentioning
confidence: 84%
See 3 more Smart Citations
“…This result may indicate that low concentrations of NAA were suitable for SE in K. paniculate. In the studies of other woody plants, the frequency of somatic embryogenesis varied from 4.9% to 63% [27][28][29]34], and the frequency of SE in K. paniculate was at a high level in the research. Similarly, NAA has been reported to influence somatic embryo development in holm oak and Eucalyptus camaldulensis Dehn.…”
Section: Effect Of Plant Growth Regulators On Somatic Embryogenesismentioning
confidence: 84%
“…In addition, studies about the effects of 2,4-D and other PGRs on embryogenic callus induction were reported. In the study about Elaeis guineensis, 2,4-D was proved to have similar effects on embryogenic callus induction to picloram [27], and similar results were also obtained in oil palm [31]. For SE, some studies showed that high 2,4-D concentrations are conducive to embryogenic callus induction and proliferation, and that the reduction or removal of 2,4-D promotes SE [32,33]; however, conflicting results were reported.…”
Section: Effect Of Plant Growth Regulators On Somatic Embryogenesismentioning
confidence: 85%
See 2 more Smart Citations
“…In the case of E. guineensis, several types of explants were already used to initiate somatic embryogenesis process: Mature or immature zygotic embryos (Balzon et al, 2013;Silva et al, 2014), cell suspensions from immature leaf segments (De Touchet et al, 1991), leaf segments (Pádua et al, 2013) and immature male inflorescence (Jayanthi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%